2022
DOI: 10.1155/2022/8975704
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, and Negative Outcomes of Anxiety and Depressive Disorders among HIV-Infected Children and Adolescents in Uganda: CHAKA Study 2014-2017

Abstract: Background. Children and adolescents infected with HIV/AIDS (CA-HIV) experience a considerable burden of depressive and anxiety disorders that have a tendency to persist into adulthood. The aim of this study was to determine the prevalence of anxiety, depression, and their clinical correlates among children and adolescents with HIV/AIDS (CA-HIV) in Uganda. Methods. A random sample of 1339 CA-HIV (ages 5-18 years) and their caregivers completed a standardized DSM-5-referenced psychiatric rating scale, the Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have highlighted the prevalence and significance of anxiety disorders among adolescents living with HIV. For instance, a study in Uganda found that the prevalence of anxiety disorders in this group was 9%, compared to 6.4% for depression (Mpango et al, 2022). Unlike depression, anxiety has also been found to have a stronger association with HIV-related stigma, a key factor in the lives of YALHIV (Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have highlighted the prevalence and significance of anxiety disorders among adolescents living with HIV. For instance, a study in Uganda found that the prevalence of anxiety disorders in this group was 9%, compared to 6.4% for depression (Mpango et al, 2022). Unlike depression, anxiety has also been found to have a stronger association with HIV-related stigma, a key factor in the lives of YALHIV (Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%